Knowledge, attitudes, and practices of pregnant women regarding COVID‐19 vaccination in pregnancy in 7 low‐ and middle‐income countries: An observational trial from the Global Network for Women and Children's Health Research. (5th June 2022) - Naqvi, Seemab; Saleem, Sarah; Naqvi, Farnaz; Billah, Sk Masum; Nielsen, Eleanor; Fogleman, Elizabeth; Peres‐da‐Silva, Nalini; Figueroa, Lester; Mazariegos, Manolo; Garces, Ana L.; Patel, Archana; Das, Prabir; et al.
Abstract: Objectives: We sought to determine the knowledge, attitudes and practices of pregnant women regarding COVID‐19 vaccination in pregnancy in seven low‐ and middle‐income countries (LMIC). Design: Prospective, observational, population‐based study. Settings: Study areas in seven LMICs: Bangladesh, India, Pakistan, Guatemala, Democratic Republic of the Congo (DRC), Kenya and Zambia. Population: Pregnant women in an ongoing registry. Methods: COVID‐19 vaccine questionnaires were administered to pregnant women in the Global Network's Maternal Newborn Health Registry from February 2021 through November 2021 in face‐to‐face interviews. Main outcome measures: Knowledge, attitude and practice regarding vaccination during pregnancy; vaccination status. Results: No women were vaccinated except for small proportions in India (12.9%) and Guatemala (5.5%). Overall, nearly half the women believed the COVID‐19 vaccine is very/somewhat effective and a similar proportion believed that the COVID‐19 vaccine is safe for pregnant women. With availability of vaccines, about 56.7% said they would get the vaccine and a 34.8% would refuse. Of those who would not get vaccinated, safety, fear of adverse effects, and lack of trust predicted vaccine refusal. Those with lower educational status were less willing to be vaccinated. Family members and health professionals were the most trusted source of information for vaccination. Conclusions: This COVID‐19 vaccine survey in seven LMICs found that knowledge about the effectiveness and safety of the vaccine was generally low but varied. Concerns about vaccine safety and effectiveness among pregnant women is an important target for educational efforts to increase vaccination rates. Tweetable abstract: The COVID‐19 vaccine survey in seven LMIC indicates that the knowledge of pregnant women about the effectiveness and safety of the vaccine was generally low and a third of the women did not plan to be vaccinated.